John Paul II and the Galileo case - ’rehabilitation’ of Galileo? - Sierotowicz, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
John Paul’s II reflection on the Galileo’s case is deeply rooted in the teaching of the Vatican Council II (GS, n. 36). It’s most profound expression one can find in the Pope’s discourse celebrating the anniversary of Einstein’s birthday given in November 1979. John Paul II emphasizes not only Galileo’s sufferings caused by the Church institutions, but also invites to examine Galileo’s case to create the appropriate conditions for the fruitful dialogue between science and theology. As a response the special commission was established in the year 1981. This commission was active until the year 1990, and her different sub-commissions (juridical, scientific, exegetic, and so on) published many valuable studies on Galileo’s case. The conclusion of commission activity was formally celebrated by the end of 1992, during the session of Pontifical Academy of Science. Cardinal Poupard and the Pope, John Paul II delivered two, very important speeches; both of them offered a slightly different syntheses of the conclusions reached by the commission, and the second one has been interpreted by the papers as a sort of rehabilitation of Galileo. The Pope interpreted the Galileo’s case as a mutual, tragic incomprehension, and stressed that, it could serve us as a lesson in the similar circumstances. And this, strictly pastoral and fostering the dialogue between science and faith approach seems to characterize John Paul’s II interpretation of the Galileo’s case.